Economies of Scale and Efficiency of the Pulp Industry in Indonesia: Cobb-douglas Cost Function Approach - Subardin, Muhammad; Susetyo, Didik; A. Kadir, Syamsurijal; Suhel, Suhel (International Journal of Economics and Financial Issues, 2018)
This study aims to analyze the economies of scale and efficiency using long-term Cobb-Douglas function model to derive coefficients that require economies of scale and efficiency in the pulp industry. The economies of scale are derived from the Cobb-Douglas Deterministic cost function model. While the level of cost efficiency is obtained from the use of Cobb-Douglas Stochastic Frontier cost function model. This study used data panel that include five companies in the pulp industry during the observation period of 2009-2014. The results show that the pulp industry reaches economies of scale but there is cost inefficiency. The factors that drive the pulp industry to have high concentrations of which are large economies of scale supported by efficiency. Despite of reaching economies of scale, cost inefficiency has occurred. The cost inefficiency indicates that the economic scale of a large pulp company is relatively not supported by the company’s ability to eliminate cost inefficiency, but the company enjoy an economies of scale advantage as reflected in production levels under the Minimum Efficient Scale (MES). it implied that an increase in industry concentration ratio, entry barriers and large capital needs enter into the pulp industry. Keywords: Cobb-Douglas Cost Function, Stochastic Frontier Analysis, Economies of Scale, Inefficiency, Minimum Efficient Scale. JEL Classiffications: D24; L11; L60